Cauliflower : over 70 exciting ways to roast, rice, and fry one of the world's healthiest vegetables - Telem, ʻOz (Hardie Grant Books, 2018)
Cauliflower is the undisputed queen of the vegetable world: nutritious, available year-round, easy to cook with and, of course, delicious. It is loved by so many, and yet, most people know of only a few ways to prepare it. In Cauliflower, Oz Telem praises this humble vegetable, and shows the varied and creative ways cauliflower can fit into your daily cooking routine. Cauliflower's unique characteristics allow it to stand in for many ingredients-it can serve as a low-carb replacement for rice, bulgur wheat and semolina, transform to a silky cream in place of dairy, come as a main course instead of chicken tenders or steak, be turned into a rich, potato-like mash and more. Beyond the recipes and captivating photography, this book places special emphasis on techniques and cooking methods, and contains a comprehensive introduction to cauliflower and its special attributes.--Provided by publisher.